Women legislators and economic performance - Thushyanthan Baskaran; Sonia R. Bhalotra; Brian Min; Yogesh Uppal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
There has been a phenomenal global increase in the proportion of women in politics in the last 20 years. While there is evidence that raising the share of women politicians has substantive impacts on the composition of government spending, there is scarcely any evidence of how it influences economic performance. We investigate this using comprehensive data on competitive elections to India's state legislative assemblies, exploiting close elections between men and women to isolate the causal effect of legislator gender in a regression discontinuity design. We identify significantly higher growth in economic activity in constituencies that elect women. Probing mechanisms, we find evidence that women legislators are less likely to be criminal and corrupt, more efficacious, and less vulnerable to political opportunism. We find no evidence of negative spillovers to neighbouring (male-led) constituencies, consistent with net growth.
Keywords: D72; D78; H44; H73; 330; women legislators; political representation; corruption; economic growth